2019
DOI: 10.1371/journal.pone.0215384
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators of communication about off periods in Parkinson’s disease: Qualitative analysis of patient, carepartner, and physician Interviews

Abstract: Background Successful patient-physician communication is critical for improving health outcomes, but research regarding optimal communication practices in Parkinson’s disease is limited. The objective of the current study was to investigate barriers and facilitators of communication between persons with Parkinson’s disease, carepartners, and physicians, specifically in the setting of off periods, with the goal of identifying ways to improve patient-carepartner-physician … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 31 publications
4
30
0
Order By: Relevance
“…We developed questionnaires (see Supplementary Material) concerning the experience, understanding and communication about OFF periods based on data collected in qualitative interviews with representatives of each of the three groups (PwP, carepartners and physicians). The interviews (results reported separately) (12), were performed to ensure that questionnaire content covered the main issues, concerns and opinions facing these three groups. The questionnaire for physicians addressed their communication practices about OFF periods with PwP and their opinions on barriers and facilitators of this communication.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We developed questionnaires (see Supplementary Material) concerning the experience, understanding and communication about OFF periods based on data collected in qualitative interviews with representatives of each of the three groups (PwP, carepartners and physicians). The interviews (results reported separately) (12), were performed to ensure that questionnaire content covered the main issues, concerns and opinions facing these three groups. The questionnaire for physicians addressed their communication practices about OFF periods with PwP and their opinions on barriers and facilitators of this communication.…”
Section: Methodsmentioning
confidence: 99%
“…Prior to the current mixed-methods study, no identified investigated barriers of communication about OFF periods. After investigating communication about OFF periods through preparatory interviews with PwP, carepartners, and physicians (12), we undertook a survey of PwP, carepartners, and physicians to understand the nature of communication about OFF periods and barriers and facilitators to communication from all three perspectives in a larger cohort. This knowledge is needed to understand the types of interventions that may be needed to support discussion about OFF periods.…”
Section: Introductionmentioning
confidence: 99%
“…In almost half of the responses, ≥1 most bothersome symptoms reported by patients would not be captured by the WOQs. Although the use of questionnaires to identify and communicate about off symptoms is seen as useful by PD patients, their care partners, and healthcare providers, our results highlight the limitations of using lists as tools in isolation to capture the patient experience in clinical practice. The results are also in keeping with the previous finding that patients with PD value the narrative interview as the most important facilitator of communication with their neurologist related to wearing off, and neurologists rate talking with their patients as the most important facilitator of discussions related to off periods .…”
Section: Discussionmentioning
confidence: 85%
“…Agreement was more likely for motor symptoms; when a figurative language phrase was interpreted as representing a nonmotor symptom, agreement for which specific symptom was represented was low. This lack of agreement on over half of phrases may reflect a combination of factors, including the heterogeneity intrinsic to PD, 23 the broad range of ways in which patients experience complex PD manifestations and communicate about them, 24 , 25 and the inherently subjective nature of interpreting figurative language. 26 These and other factors may lead to misunderstandings in communication about off periods and, in turn, their suboptimal detection 12 and treatment.…”
Section: Discussionmentioning
confidence: 99%